MANFAAT ALUTSISTA RADAR DALAM MENDUKUNG SISTEM PERTAHANAN UDARA BERLAPIS TNI AU - Meylia Susiana Dewi Putri; Rudy A.G. Gultom; Achmad Farid Wajdji (DAS Institute, 2022)
Science and technology show a trend that continues to develop. This has an impact on tools such as defense equipment produced or owned by a country to be more sophisticated. A country must have a defense system that can protectthe entire terriroty of the country,one of which is its airspace. Violations in the airspace often occur because the defense system is still weak. One of the tools that play a role in conducting surveillance for airspace is Radar. Currently, Indonesia still has several blank spot areas that are not detected by Radar. This needs to be solverd by placing Radar in some areas that cannot be detected or blank spot areas using a geographic information system (GIS). GIS is one of the platforms used in mapping without having to survey the location directly.